Examination for the factors contribute to joint effusion in patients with internal derangement on temporomandibular joint disorder - Fumi Mizuhashi; Ichiro Ogura; Yuko Watarai; Tatsuhiro Suzuki; Ryo Mizuhashi; Makoto Oohashi; Hisato Saegusa (Wolters Kluwer Medknow Publications, 2022)
Background/Aim: The aim of this study was to investigate the factors contribute to the joint effusion in the patients with internal derangement on temporomandibular joint (TMJ) disorder. Methods: We reviewed the 83 TMJs that were diagnosed as internal derangement (anterior disc displacement with or without reduction) by magnetic resonance imaging. Joint effusion was diagnosed using T2-weighted images. The differences in the presence of joint effusion according to the gender, age, diagnosis, and TMJ pain were analyzed using cross-tabulation or Mann-Whitney test. The relationship between joint effusion and gender, age, diagnosis, and TMJ pain was analyzed by logistic multivariate regression analysis. Results: The presence of joint effusion was larger on anterior disc displacement without reduction (χ2[1] = 7.47, P = 0.006) and the TMJ with pain (χ2[1] = 7.50, P = 0.006). The results of logistic multivariate regression analyses indicated that the diagnosis of anterior disc displacement without reduction was signiﬁcant in TMJ with joint effusion (odds ratio = 3.299, P = 0.036) and the TMJ with pain was also signiﬁcant in TMJ with joint effusion (odds ratio = 4.413, P = 0.007). The gender and age showed no relationships with joint effusion. Conclusions: The results of this study made it clear that joint effusion was easier to occur in the TMJ of anterior disc displacement without reduction and in the TMJ with pain. Anterior disc displacement without reduction and TMJ pain would be related to the higher risk of joint effusion.